35q^(-3/5)=-21q^(-8/5)-((-21q^8/5)*35q^(-3/5))
Re-arrange and solve for q. I did it but got some mad answer.
Hello,
Let's put it all in one side :
$\displaystyle 35q^{-3/5}+21q^{-8/5}+({\color{red}(-21q^{8/5})*35q^{-3/5}})=0$
Look at the red thing
$\displaystyle -21q^{8/5}*35q^{-3/5}=-(21*35)q^{8/5-3/5}=-21*35 q^1=-21 \cdot 35 \cdot q$
Hence the equation is now :
$\displaystyle 35q^{-3/5}+21q^{-8/5}-21 \cdot 35 \cdot q=0$
Multiplying everything by $\displaystyle q^{8/5}$, we get :
$\displaystyle 35q^1+21q^0-21\cdot 35 \cdot q^{13/5}=0$
$\displaystyle 35q+21-21\cdot 35 \cdot q^{13/5}=0$
I got mad answers too